M2 Pseudomonas aeruginosa (Pa) biofilm-forming potential and metabolomic phenotypes differ between chronically infected patients with cystic fibrosis (CF) and non-CF bronchiectasis (Bx). (12th November 2019) - Smith, WD; Murphy, RA; Simbo, A; Fletcher, OL; Cameron, SJS; Bardin, EE; Takats, Z; Hogg, C; Filloux, A; Bush, A; Davies, JC
Abstract : Chronic Pa infection in CF is linked to biofilm formation in the airways and there is modest evidence for this process in Bx. Pa demonstrates numerous other phenotypes which may play a role in enabling persistence in these diseases. We have previously demonstrated that Pa metabolome and virulence-related metabolites, including rhamnolipids and quorum sensing molecules, can be characterized using direct-from-sample mass spectrometry. 1 We hypothesized that these techniques would demonstrate disease specific differences in Pa strain characteristics. Methods: Pa strains from chronically infected patients (CF, n=70; Bx from all causes, including idiopathic Bx, but excluding CF, n=70) were cultured in rich media in a static crystal violet biofilm assay before measuring adherent biofilm biomass. Growth over the same time period was assessed for each strain. Separately Pa strains were cultured on agar before laser assisted mass spectrometry analysis. Results: CF strains demonstrated 1.7 fold greater biofilm biomass than Bx strains (p=0.02). Biofilm biomass correlated with bacterial growth rate (Spearman r 0.64 (95% CI 0.53–0.73), p<0.0001) though the increased biofilm biomass of CF strains persisted after growth correction. Mass spectrometry analysis was successful in 126 Pa strains. As observed before, there was considerable overlap in the principle component analysis of CF and Bx Pa metabolome. A supervised partial least squares-discriminant analysis (PLS-DA) demonstrated separation of the groups. Five component cross validation accuracy 0.89, R2=0.81, Q2=0.63. In future, we hope to identify the spectral features causing this separation. Conclusion: We demonstrated differences in Pa biofilm biomass and metabolome from CF and Bx patients, which may relate to variation in Pa airway adaptation. Possible explanations include pathophysiological (eg. surface liquid composition, pH) or therapeutic differences (eg. drugs to aid airway clearance, short and long-term antibiotics). Understanding features of Pa adaptation in CF and Bx could lead to identification of biomarkers of disease severity and novel approaches to treat Pa airway infection. Supported by the British Lung Foundation. Affiliated to the UK CF Trust-funded Strategic Research Centre for Pseudomonas infection. Reference: Bardin EE, et al . Sci. Rep . 2018;8(1):10952.